RANCANG BANGUN SISTEM MANAJEMEN PERSEDIAAN PRODUK HADIAH UNTUK DUKUNGAN DIVISI PEMASARAN PADA KANTOR CABANG PT. FAJAR LESTARI SEJATI DENGAN PENERAPAN TEKNOLOGI QR CODE BERBASIS WEB - Kinanti Sekar Arum; Maya Utami Dewi; Migunani Migunani; Khoirur Rozikin; Febryantahanuji Febryantahanuji (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
PT. Fajar Lestari Sejati was a company engaged in the field of door and window accessories, offering its products from store to store, small projects, and even entering large-scale projects. PT. Fajar Lestari Sejati was still managing promotional goods manually in the marketing division, encountering difficulties in tracking or checking goods entering and leaving the warehouse. Additionally, there were discrepancies between the physical stock and the recorded data. The purpose of this research was to design an inventory management system for promotional products to support the marketing division at PT. Fajar Lestari Sejati's branch office by implementing QR Code technology. This research resulted in a web-based application integrated with a database, providing users with easy and fast access to perform data entry, transactions, and reporting processes related to inventory control.